Malnutrition among children raises intimidation to their health in Bangladesh: control strategies - Nayeem, Jannatul; Mamun, Md Abdullah Al; Sultan, Safayet; Ray, Subir Chandro; Ahammed, Tanvir; Borty, Shuvho Chakra (Asian Journal of Medical and Biological Research, 2020)
Nutritional status of children is a momentous issue across the world. Children are mostly suffering from various infectious diseases, which are ensuing through malnutrition or incommensurable nutritional requirement of children. Household food security, caring practice for women and children, health environment and services and infectious diseases are the major cause of mortality particularly in children in many developing countries. The findings of the review clearly relate malnutrition, which is one of the most underlying causes of infectious diseases among children and existing evidence shows that the prevalence of under-nutrition and other forms of malnutrition among under-five children was high and they are easily affected by infectious disease such as diarrhea, measles, malaria, acute respiratory infection etc.A well-designed social protection system has great potential to improve malnutrition in Bangladesh. The international and domestic evidence presented in this review clearly demonstrates the importance of an integrated approach to tackling malnutrition in Bangladesh. Severe wasting may be reduced by simply improving food intake but tackling chronic malnutrition requires integrated social protection programmes. Programmes that have effectively reduced stunting and wasting have also addressed many of the underlying causes of malnutrition, including improving household food security and the health environment. Asian J. Med. Biol. Res. June 2019, 5(4): 237-245